PENGARUH INFLASI, SUKU BUNGA DAN NET INTEREST MARGIN TERHADAP EARNING PER SHARE PADA PT. BANK CENTRAL ASIA TBK PERIODE 2005-2023 - Nur Rohimah, Venti; Surahaman, Arif (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the effect of inflation, interest rates, and Net Interest Margin (NIM) on Earnings Per Share (EPS) at PT. Bank Central Asia Tbk over the period 2005-2023. The method used in this study is quantitative with a multiple linear regression approach. The data used are secondary data obtained from the annual financial reports of PT. Bank Central Asia Tbk and other official publications. The results show that inflation and interest rates have a negative and significant effect on EPS, while NIM has a positive and significant effect on EPS. Simultaneously, these three variables have a significant effect on EPS. These findings indicate that macroeconomic variables and internal bank performance play an important role in determining the company's stock profitability.